Multifunctional Nanovehicles for Combined 5-Fluorouracil and Gold Nanoparticles Based on the Nanoprecipitation Method - Karmi, Abeer (2011)
To facilitate the administration of combined 5-Fluorouracil (5-FU) and gold nanoparticles (for photothermal treatment purposes), we developed 5-FU-gold-poly(lactide-co-glycolic acid) (5-FU-Au- PLGA) nanovehicles, via the nanoprecipitation method. The gold nanoparticles were incorporated inside the 5-FU-PLGA carriers using a roller mixer. Morphological analysis using atomic force microscopy (AFM), scanning electron microscopy (SEM) and transmission electron microscopy (TEM), indicated uniform, singly separated spherical nanoparticles (NPs). Drug content, recovery and entrapment in the NPs were approximated using UV-spectrophotometer data. Approximately 26% of nanoparticles were recovered after drying. The percentage of total drug content was about 30%, and the percentage of drug entrapment reached 57%. Electrostatic Force Microscopy images confirmed the presence of gold inside the drug-loaded nanoparticles. We speculate that the 20-nm gold particles were able to diffuse, after 12 hours of mixing (using the roller mixer), into the PLGA matrix through the 100-nm pores (observed by SEM) without affecting the integrity of the drug delivery vehicle. These synthesized nanoparticles show promise as multimodal vehicles in the delivery of chemotherapeutic agents.